Corporate governance mechanism and Corporate Social Responsibility disclosure: evidence from emerging market - Nugraheni, Peni; Budhiani, Annisa Balqis; Jamil, Nurul Nazlia (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
This research aims to examine the influence of the board of directors and the audit committee on Corporate Social Responsibility (CSR) disclosure. The board of directors is proxied by board size, board meeting frequency, and board gender diversity. Meanwhile, the audit committee is proxied by audit committee size, audit committee meeting frequency, and audit committee expertise. The data used in this research are secondary data originating from the annual reports of non-financial companies listed on the Indonesia Stock Exchange (IDX) and the Saudi Exchange. This research adopts a quantitative research approach, with data collection techniques including literature study and documentation. The data are analyzed using panel data regression analysis. The results of the panel data regression analysis show that board size and audit committee expertise have a positive but insignificant effect on CSR disclosure. Meanwhile, board meetings and audit committee size have a positive and significant effect on CSR disclosure. Furthermore, board gender diversity and audit committee meeting frequency have a negative and significant effect on CSR disclosure. This research contributes by providing insights into the role of corporate governance mechanisms in encouraging corporate transparency through CSR disclosure. The findings are expected to provide a better understanding of how governance structures influence companies in disclosing their social and environmental responsibilities.